Corporate Social Responsibility: A Restrictive Approach for the Management of Human Resources - Ouddasser, Abderrahmane; Mellouki, Anass; Belyagou, Yassine (International Journal of Engineering and Technology, 2019)
The corporate social responsibility plays a key role in improving the image of the company and sustaining its activities. This concept must be taken into account in relation to human resources management.
Keywords: corporate social responsibility (CSR); management of human resources (MHR); sustainable development (SD)